Impact of fib-4 index on outcomes after lvad implantation - Şener, Yusuf Ziya; Yazar, Arzu; Karaca, İbrahim Oğuz (My University, 2024)
...
Keywords: FIB-4; LVAD Implantation; Cardiac; Cardiovascular Systems